Relation between C reactive protein concentrations and coronary microvascular endothelial function. Issue 7 (14th June 2004) - Teragawa, H; Fukuda, Y; Matsuda, K; Ueda, K; Higashi, Y; Oshima, T; Yoshizumi, M; Chayama, K
Abstract : Objective: To determine how C reactive protein (CRP), a sensitive marker of inflammation, is related to coronary endothelial function. Design: Changes in quantitative coronary angiographic findings and Doppler flow velocity measurements in response to locally infused acetylcholine were assessed. Setting: Tertiary cardiology centre. Patients: 46 patients with angiographically normal coronary arteries were divided into groups with normal (⩽ 3 mg/l) or increased (> 3 mg/l) CRP concentrations. Interventions: Acetylcholine (3 and 30 μg/min) was infused into the left coronary ostium for two minutes. Main outcome measures: Percentage change in diameter of epicardial coronary arteries and coronary blood flow (CBF) in response to acetylcholine; and correlations between these parameters and serum CRP concentrations. Results: 15 patients had increased CRP concentrations. The change in coronary artery diameter induced by acetylcholine infusion was similar between the groups but the increase in CBF induced by acetylcholine was smaller in patients with increased CRP concentrations (54.9% v 139.4% with acetylcholine 30 μg/min, p = 0.0030). Multivariate analysis identified increased CRP concentration as independently associated with attenuated CBF response to acetylcholine at 30 μg/min (p = 0.0078, R 2 = 0.434). Conclusions: These findings suggest that inflammation appears to be associated with impaired coronary endothelial function in resistance but not conduit vessels. The data suggest a close relation between chronic vascular inflammation and endothelial dysfunction in atherosclerosis.